2007
DOI: 10.1189/jlb.0207095
|View full text |Cite
|
Sign up to set email alerts
|

The association of ICAM-1 Exon 6 (E469K) but not of ICAM-1 Exon 4 (G241R) and PECAM-1 Exon 3 (L125V) polymorphisms with the development of differentiation syndrome in acute promyelocytic leukemia

Abstract: The use of all trans-retinoic acid (ATRA) is the basis of treatment of acute promyelocytic leukemia (APL) and represents the paradigm of differentiation therapy. In general, ATRA is well-tolerated but may be associated with a potentially lethal side-effect, referred to as retinoic acid or differentiation syndrome (DS). The cellular and molecular mechanisms of DS are poorly understood and involve changes in the adhesive qualities and cytokine secretion of leukemic cells during ATRA-induced differentiation. As l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
0
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 22 publications
2
22
0
1
Order By: Relevance
“…Some researchers have highlighted the importance of ICAM-1 in building up excessive inflammation in DS. Dore et al reported that DS syndrome was related to some genotype with ICAM-1 [13], and Cunha De Santis et al found that ICAM-1 gene knockout abolished ATRA-caused inflammation-related syndrome in mice [14]. In light of this information and our own observations, we believe that ICAM-1 inhibition may be the major factor in celastrol’s action of preventing cell infiltration in lungs, though reductions in cytokines secretion may also contribute to this result.…”
Section: Discussionsupporting
confidence: 56%
See 2 more Smart Citations
“…Some researchers have highlighted the importance of ICAM-1 in building up excessive inflammation in DS. Dore et al reported that DS syndrome was related to some genotype with ICAM-1 [13], and Cunha De Santis et al found that ICAM-1 gene knockout abolished ATRA-caused inflammation-related syndrome in mice [14]. In light of this information and our own observations, we believe that ICAM-1 inhibition may be the major factor in celastrol’s action of preventing cell infiltration in lungs, though reductions in cytokines secretion may also contribute to this result.…”
Section: Discussionsupporting
confidence: 56%
“…Such expectancy is encouraged by our pre-experiment, which showed that celastrol could inhibit ATRA-caused ICAM-1 expression [12]. This is of importance considering that ICAM-1 plays a fundamental role in ATRA treatment-caused hyper-inflammation [13], [14].…”
Section: Introductionmentioning
confidence: 70%
See 1 more Smart Citation
“…10,23,26,27,29 In addition, DS is often associated with the development of hyperleukocytosis, pulmonary edema, generalized edema, headache, and bone pain. 10,23,26,27,29,30 The diagnosis DS has proven to be difficult because none of the aforementioned symptoms is pathognomonic of the syndrome and can be the result of concurrent medical problems, such as bacteremia, sepsis, pneumonia, pulmonary hemorrhage, or congestive heart failure. 32,33 Therefore, DS may be underdiagnosed as well as overdiagnosed.…”
Section: Introductionmentioning
confidence: 99%
“…22 DS is reported in 2.5% to 31% of the APL patients who receive induction therapy with ATRA and/or ATO. [5][6][7]10,14,16,19,20,[23][24][25][26][27][28][29][30] DS is not observed during consolidation or maintenance therapy with ATRA and/or ATO in APL patients, nor is DS observed during ATRA treatment in non-APL malignancies, implicating that the APL cells play a crucial role in the development of DS. 6,7,14,20,23,26,27,31 DS is characterized by respiratory distress, unexplained fever, weight gain, interstitial pulmonary infiltrates, pleural or pericardial effusions, hypotension, and acute renal failure.…”
Section: Introductionmentioning
confidence: 99%